Real numbers only

Algebra Level 2

If a , b , c a,b,c are real numbers and a + b + c = 0 a+b+c=0 then the value c y c a , b , c a ( b c ) 3 \sum_{cyc}^{a,b,c}a(b-c)^{3}


The answer is 0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Gian Sanjaya
Oct 8, 2015

We can expand and separate the expression into:

c y c a , b , c a ( b c ) 3 = c y c a , b , c a b 3 3 a b 2 c + 3 a b c 2 a c 3 \displaystyle \sum_{cyc}^{a, b, c} a(b-c)^3=\displaystyle \sum_{cyc}^{a, b, c} ab^3-3ab^2 c+3abc^2-ac^3

c y c a , b , c a ( b c ) 3 = c y c a , b , c ( a b 3 a c 3 ) 3 a b c c y c a , b , c ( c b ) \displaystyle \sum_{cyc}^{a, b, c} a(b-c)^3=\displaystyle \sum_{cyc}^{a, b, c} (ab^3-ac^3) - 3abc \displaystyle \sum_{cyc}^{a, b, c} (c-b)

c y c a , b , c a ( b c ) 3 = a b 3 b a 3 + b c 3 c b 3 + c a 3 a c 3 ( 3 a b c ) ( 0 ) = c y c a , b , c a b ( b a ) ( b + a ) \displaystyle \sum_{cyc}^{a, b, c} a(b-c)^3=ab^3-ba^3+bc^3-cb^3+ca^3-ac^3 - (3abc)(0) =\displaystyle \sum_{cyc}^{a, b, c} ab(b-a)(b+a)

c y c a , b , c a ( b c ) 3 = c y c a , b , c a b ( b a ) ( c ) = a b c c y c a , b , c ( b a ) \displaystyle \sum_{cyc}^{a, b, c} a(b-c)^3=\displaystyle \sum_{cyc}^{a, b, c} ab(b-a)(-c)=-abc \displaystyle \sum_{cyc}^{a, b, c} (b-a)

c y c a , b , c a ( b c ) 3 = ( a b c ) ( 0 ) = 0 \displaystyle \sum_{cyc}^{a, b, c} a(b-c)^3=(-abc)(0) = \boxed{0}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...